Women's fiqh supplements in Islamic religious education for elementary school students - Khumayroh, Siti; Sa’diyah, Maemunah; Kamal, Muhamad Royhan (Tawazun: Jurnal Pendidikan Islam, 2026)
The discussion of women’s fiqh is a crucial aspect of Islamic Religious Education because it relates to young girls’ understanding of biological changes and Sharia law from an early age. This study aims to analyze the concepts, importance, and scope of women’s fiqh as a foundation for developing educational supplements for elementary school students. The study employs a qualitative approach using a literature review method, involving the examination of various scholarly sources such as journals, fiqh texts, and relevant educational documents from 2015 to 2024. Data were analyzed using thematic synthesis and critical evaluation techniques to identify patterns, gaps, and instructional material needs. The results indicate that education regarding menstruation, postpartum bleeding, puberty, and purification rituals is crucial to be provided systematically and in accordance with children’s developmental stages. Additionally, a gap was identified in teaching materials, specifically the absence of simple, contextual, and practical women’s fiqh supplements at the elementary school level. In conclusion, the development of women’s fiqh supplements is necessary to support learning that not only enhances religious understanding but also fosters self-awareness, health, and spiritual readiness among students as they navigate puberty in accordance with Islamic teachings. Abstrak Pembahasan fiqih wanita menjadi aspek penting dalam Pendidikan Agama Islam karena berkaitan dengan pemahaman anak perempuan terhadap perubahan biologis dan hukum syariat sejak usia dini. Penelitian ini bertujuan untuk menganalisis konsep, urgensi, serta ruang lingkup fiqih wanita sebagai dasar pengembangan suplemen pembelajaran bagi siswa sekolah dasar. Penelitian menggunakan pendekatan kualitatif dengan metode studi kepustakaan melalui penelusuran berbagai sumber ilmiah seperti jurnal, kitab fiqih, dan dokumen pendidikan yang relevan pada rentang tahun 2015–2024. Data dianalisis menggunakan teknik sintesis tematik dan evaluasi kritis untuk mengidentifikasi pola, kesenjangan, serta kebutuhan bahan ajar. Hasil penelitian menunjukkan bahwa edukasi terkait haid, nifas, pubertas, dan tata cara bersuci sangat penting diberikan secara sistematis dan sesuai perkembangan anak. Selain itu, ditemukan adanya kekosongan bahan ajar berupa suplemen fiqih wanita yang sederhana, kontekstual, dan aplikatif di tingkat sekolah dasar. Kesimpulannya, pengembangan suplemen fiqih wanita diperlukan untuk mendukung pembelajaran yang tidak hanya meningkatkan pemahaman keagamaan, tetapi juga membangun kesadaran diri, kesehatan, dan kesiapan spiritual peserta didik dalam menghadapi masa pubertas sesuai ajaran Islam.